2019
DOI: 10.6000/1929-7092.2019.08.06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender-Based Violence Towards Young Females: The Case of Vhufuli Village in Thohoyandou, Limpopo Province-South Africa

Abstract: Gender based violence towards young women is a pandemic experienced mostly by women of all classes and age in different settings, spheres of life and environment. It affects the victim both socially, emotionally, psychologically and physically. Gender based violence is caused by various factors such as substance abuse, lack of education as well as gender norms, socialization and aggressive behavior of men. This study explored the experiences of young women regarding gender-based violence and factors that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Additionally, Jacobs (2012) indicated that despite what is stated in various South African educational documents, South African schools do not promote democracy and the preservation of human rights. Similarly, Thobejane (2019) pointed out that gender-based violence is a violation of human rights. Thobejane (2019) also noted that even though gender-based violence violates human rights, societies, communities, and residents either personally experience it or observe it in their families and neighbourhoods and feel helpless to stop it.…”
Section: Theme 1: Girls' Inability To Exercise Human Rights and Their...mentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, Jacobs (2012) indicated that despite what is stated in various South African educational documents, South African schools do not promote democracy and the preservation of human rights. Similarly, Thobejane (2019) pointed out that gender-based violence is a violation of human rights. Thobejane (2019) also noted that even though gender-based violence violates human rights, societies, communities, and residents either personally experience it or observe it in their families and neighbourhoods and feel helpless to stop it.…”
Section: Theme 1: Girls' Inability To Exercise Human Rights and Their...mentioning
confidence: 99%
“…Urban and Teise (2015) cautioned once more that a safe, orderly, and clean school environment is essential for successful teaching and learning. However, Thobejane (2019) argues that to combat gender-based violence, policymakers must control the laws that will be implemented. Thus the Power Control Theory will be the solution.…”
Section: Theme 5: Strategies To Curb Gender-based Violence In Seconda...mentioning
confidence: 99%
See 2 more Smart Citations